A model of negotiated transfer pricing - Vaysman, Igor (Journal of Accounting and Economics, 1998)
A large majority of firms employ negotiated transfer pricing, yet this method of decentralization remains largely unexplored. This study develops a model of negotiated transfer pricing incorporating private divisional information, as this is the setting where decentralization is most compelling. The firm designs a compensation system utilizing divisional performance evaluation and negotiated transfer pricing. A dynamic bargaining model is employed to capture managerial negotiations. The study demonstrates that the firm can design managerial-compensation schemes and bargaining infrastructures so that the negotiated transfer-pricing structure allows it to reach the upper bound on available profits.